HUBUNGAN SEDENTARY LIFESTYLE DENGAN KEPATUHAN MENGKONSUMSI TABLET TAMBAH DARAH PADA REMAJA PUTRI DI SMK BABUNNAJAH PANDEGLANG BANTEN - Puteri, Ayu Mandala; Iskandar, Arik; Fahriati, Andriyani Rahmah (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2025)
ABSTRACT.Sedentary lifestyle is a lifestyle with the characteristics of low levels of physical activity. Sedentary lifestyle is related to all types of light activities that require the same amount of energy expenditure as resting physical activity, which is 1-1.5 METs. Compliance according to the World Health Organization (WHO) is how well a person behaves in using drugs, following a diet or changing lifestyle according to the treatment regimen. The purpose of this study is to determine the relationship between sedentary lifestyle and adherence to consuming blood supplement tablets in adolescent girls at SMK Babunnajah Pandeglang Banten. Methods This study uses quantitative research with a cross sectional design. Sampling uses the probability sampling technique using proportionate stratified random sampling with a sample of 81 respondents. Data analysis uses the Chi Square test with a degree of significance p 0.05. The results of the study were known that from 81 respondents, more than half of the respondents obtained a high sedentary lifestyle amounting to 54 respondents (66.7%) and compliance with consuming low blood supplement tablets as many as 46 respondents (56.8%). The results of the statistical test were obtained (P Value = 0.002 0.05). The conclusion is that there is a relationship between sedentary lifestyle and adherence to consuming blood supplement tablets in adolescent girls at SMK Babunnajah Pandeglang Banten. The suggestions from the results of this study are expected to be an additional reference for nurses and other health workers about sedentary lifestyle with adherence to consuming blood supplement tablets in adolescent girls.ABSTRAKSedentary lifestyle adalah kebiasaan hidup dengan karakteristik tingkat aktifitas fisik yang rendah. Sedentary lifestyle berkaitan dengan semua jenis aktivitas ringan yang membutuhkan jumlah pengeluaran energi sama dengan aktivitas fisik istirahat yaitu 1-1,5 METs. Kepatuhan menurut World Health Organization (WHO) adalah seberapa baik perilaku seseorang dalam menggunakan obat, mengikuti diet atau mengubah gaya hidup sesuai tata laksana terapi. Tujuan Penelitian ini adalah untuk mengetahui hubungan sedentary lifestyle dengan kepatuhan mengkonsumsi tablet tambah darah pada remaja putri di SMK Babunnajah Pandeglang Banten. Metode Penelitian ini menggunakan penelitian kuantitatif dengan desain cross sectional. Pengambilan sampel menggunakan teknik probability sampling dengan menggunakan proportionate stratified random sampling dengan jumlah sampel sebanyak 81 responden. Analisan data menggunakan uji Chi Square dengan derajat kemaknaan p 0,05. Hasil Penelitian diketahui dari 81 responden lebih dari setengah responden didapatkan sedentary lifestyle tinggi berjumlah 54 responden (66.7%) dan kepatuhan mengkonsumsi tablet tambah darah rendah sebanyak 46 responden (56,8%). Hasil uji statistic diperoleh (P Value = 0,002 0,05). Kesimpulan bahwa terdapat hubungan antara sedentary lifestyle dengan kepatuhan mengkonsumsi tablet tambah darah pada remaja putri di SMK Babunnajah Pandeglang Banten. Saran dari hasil penelitian ini diharapkan dapat menjadi referensi tambahan bagi perawat dan tenaga kesehatan yang lainnya tentang sedentary lifestyle dengan kepatuhan mengkonsumsi tablet tambah darah pada remaja putri.